2022
DOI: 10.1111/hsc.13988
|View full text |Cite
|
Sign up to set email alerts
|

Exploring nurse‐sensitive patient outcomes in Dutch district nursing care: A survey study

Abstract: There is a lack of evidence to guide district nurses in using nurse‐sensitive patient outcomes as it is unclear how these outcomes are currently used in daily district nursing practice. Therefore, we aimed to explore (1) which nurse‐sensitive patient outcomes are measured and how these outcomes are measured, (2) how district nurses use the outcomes to learn from and improve current practice and (3) the barriers and facilitators to using outcomes in current district nursing practice. An exploratory cross‐sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
1
0
2
Order By: Relevance
“…Such a demand can be identified in recent literature. A Dutch study that explored sensitive outcome use by nurses concluded that there is a lack of information on how nurses can and should be supported by outcome measurement tools ( 10 ) . In pediatric nursing, a literature review presented a total of 57 sensitive outcomes for use in the specialty ( 11 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Such a demand can be identified in recent literature. A Dutch study that explored sensitive outcome use by nurses concluded that there is a lack of information on how nurses can and should be supported by outcome measurement tools ( 10 ) . In pediatric nursing, a literature review presented a total of 57 sensitive outcomes for use in the specialty ( 11 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Identifica-se, na literatura recente, tal demanda. Estudo holandês que explorou a utilização de resultados sensíveis por enfermeiras concluiu que falta informações sobre como as enfermeiras podem e devem ser apoiadas por instrumentos de medidas de resultados (10) . Na área da enfermagem pediátrica, revisão de literatura apresentou um total de 57 resultados sensíveis para uso na especialidade (11) .…”
Section: Inovações E Contribuições Do Conteúdo Dos Capítulos Da Normaunclassified
“…Esta demanda se identifica en la literatura reciente. Un estudio holandés que exploró el uso de resultados sensibles por parte de los enfermeros concluyó que falta información sobre cómo los enfermeros pueden y deben recibir apoyo de los instrumentos de medición de resultados (10) . En el área de enfermería pediátrica, una revisión de la literatura presentó un total de 57 resultados sensibles para su uso en la especialidad (11) .…”
Section: Innovaciones Y Aportes Del Contenido Introductorio De La Normaunclassified